TRANSLATION THEORY AND PRACTICE: WITH THE EXAMPLE OF IDIOMS - Ababakirova Marjona Sherzodbek qizi (Western European Studies, 2024)
The foundation of the multilingual and multicultural environment is translation theory and practice, which promotes efficient communication and comprehension across cultural boundaries. This abstract explores the complex relationships that exist between translation theory, guiding concepts, and real-world applications in the ever-changing field of language transfer. This paper explores the theoretical underpinnings of the art of translation, working through important ideas including cultural translation, equivalency, and the influence of technology on translation techniques. It looks at the changing ideas and methods in translation theory and clarifies how these affect the real-world applications of translation.
Keywords: Translation theory; Translation practice; Skopos; Hans J. Vermeer